Problemy nacal'nogo otbora junych prygunov v vodu - Raspopova, E. V. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2015)
The article considers the problems of the initial selection of children to practice diving in specialized children and youth sports schools. The author provides data of model characteristics of divers of high class and also the basic criteria for the initial selection and the age for enrollment in the groups of initial training.